(untitled) (Conference Zone, 2022)
The choice of a profession is one of the most important choices of a person, which determines the life path. It is necessary that the profession correspond to the interests of the individual, but its choice must be justified, as far as the person meets the requirements of the profession. Adolescents have to solve problems: who to be, what to be and how to implement it. Therefore, they turn to the social experience of other people, focus on the assessment of others, while the main source of knowledge is the media and the Internet. Helping young people in choosing a profession, preparing the younger generation for creative work for the benefit of society is the most important task of general and additional education.